2022
DOI: 10.3389/fnagi.2022.832700
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Character of Plasma Amyloid Beta Over the Course of Cognitive Decline in Alzheimer’s Continuum

Abstract: Plasma amyloid-β (Aβ) was associated with brain Aβ deposition and Alzheimer’s disease (AD) development. However, changes of plasma Aβ over the course of cognitive decline in the Alzheimer’s continuum remained uncertain. We recruited 449 participants to this study, including normal controls (NC), subjective cognitive decline (SCD), mild cognitive impairment (MCI), AD, and non-AD dementia. All the participants underwent plasma Aβ42, Aβ40, and t-tau measurements with single-molecule array (Simoa) immunoassay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…As a new screening strategy, plasma AD biomarkers are reported to have comparable diagnostic efficacy with gold standard methods 25–31 . In a previous study, plasma Aβ42 showed an increasing trend in normal to subjective cognitive decline before decreasing in mild cognitive impairment (MCI) and AD 32 . This reported biphasic change is similar to our results, in which plasma Aβ42 was slightly elevated but not significant in newly diagnosed MMD patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a new screening strategy, plasma AD biomarkers are reported to have comparable diagnostic efficacy with gold standard methods 25–31 . In a previous study, plasma Aβ42 showed an increasing trend in normal to subjective cognitive decline before decreasing in mild cognitive impairment (MCI) and AD 32 . This reported biphasic change is similar to our results, in which plasma Aβ42 was slightly elevated but not significant in newly diagnosed MMD patients.…”
Section: Discussionsupporting
confidence: 89%
“…[25][26][27][28][29][30][31] In a previous study, plasma Aβ42 showed an increasing trend in normal to subjective cognitive decline before decreasing in mild cognitive impairment (MCI) and AD. 32 This reported biphasic change is similar to our results, in which plasma Aβ42 was slightly elevated but not significant in newly diagnosed MMD patients.…”
Section: Brain Perfusion Cognition and Ad-like Pathological Burdensupporting
confidence: 91%
“…Furthermore, the predictive value of plasma Aβ for brain amyloid deposition is inconsistent throughout cognitive decline. [ 35 ] In a retrospective clinical study, lower Aβ40 and Aβ42 levels were associated with more significant cognitive decline, based on the patient's 3-year changes in the Montreal Cognitive Assessment and Cambridge Cognitive Examination. [ 36 ] The significant positive correlation between elevated plasma Aβ levels and improvements in subjective and objective cognitive indicators may reflect a functional relationship similar to that between cerebral Aβ burden and memory complaints and/or cognitive performance in cross-sectional studies of older adults without dementia.…”
Section: Potential Biomarkersmentioning
confidence: 99%
“…In the AD continuum, plasma Aβ42 showed a significantly increasing trend from NC to SCD, before decreasing in the MCI and AD stages. Furthermore, the predictive value of plasma Aβ for brain amyloid deposition is inconsistent throughout cognitive decline [35] . In a retrospective clinical study, lower Aβ40 and Aβ42 levels were associated with more significant cognitive decline, based on the patient's 3-year changes in the Montreal Cognitive Assessment and Cambridge Cognitive Examination [36] .…”
Section: Potential Biomarkersmentioning
confidence: 99%
“…Accordingly, it is unclear whether the current SCD research definition is equally suited for Eastern populations, or needs tailoring regarding cultural appropriateness and specificity for the target population 7 . To harmonize SCD research across cultures, Sino‐German conferences took place (2016, 2017, 2019), 8 and Chinese SCD cohorts were established using a contemporary SCD research definition 9–12 . Beyond adherence to the general SCD definition, various SCD‐related features 1,2 were coded, and their predictive value for amyloid burden was tested in Chinese SCD subjects 13,14 .…”
Section: Introductionmentioning
confidence: 99%